Kajian Karakteristik dan Asupan Cairan pada Atlet di SMA Negeri 1 Sewon - Fani Indrawati; Weni Kurdanti; Isti Suryani (JURNAL NUTRISIA, 2017)
Background: the fulfillment of energy needs and liquids athletes of nutritional intake and the fluid that adekuat is the most frequently forgotten by athletes .Needs of water per different people , are influenced by various factors like sex , age , the activity , as well as the environment .Fluid loss as many as 3 to 5% of weight resulting in interference function cardiovascular diseases that would have a direct impact on sports performance Objective: this research aims to understand the characteristics of athletes based on fluid intake on athletes in SMA Negeri 1 Sewon. Method : the kind of research is observational with the design research cross sectional.Aspects subjects covering liquid intake, age, sex, BMI and kind of sport in athletes in any kind a sport that followed.Using a technique technique sampling random stratification.Any species of sports taken as the sample.The sample of the a total of 49 respondents. Research conducted was taken from the results of interviews respondents by the SQ FFQ. Results : liquid intake in an athlete based on kinds of sports and characteristic of (the age, sex, BMI), known of 73,5 % athletes with liquid intake less. Liquid intake the average athletes was 2963,4 ml per day, with intake at least 1412,1 ml and intake maximum 4867,9 ml and standard deviations 884,15. Conclusions : Based on characteristic (age, sex, BMI) and kinds of sports, athletes with liquid intake less (73,5 %). Keywords : characteristics athletes, kind of sports, liquid intake